-8x2+7x+12
2007-05-18 08:07:12
·
answer #1
·
answered by ~♥~ 2
·
0⤊
0⤋
Assume question is:-
x² - 9x² + 7x + 12
= 12 + 7x - 8x²
However could be read as:-
x² - 18 + 7x + 12
= x² + 7x - 6
2007-05-18 08:15:52
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
=x2-18+7x+12
=x2+7x-18+12
=x2+7x-6
(assuming '-9x2' is 9 multiply by 2)
2007-05-18 08:09:41
·
answer #3
·
answered by shipdada 3
·
0⤊
0⤋
x^2 - 9x^2 + 7x + 12 =
combine like terms
-8x^2 + 7x + 12
and it does not simplify further
2007-05-18 08:09:12
·
answer #4
·
answered by Poetland 6
·
0⤊
0⤋
x^2-18+7x+12=x^2+7x-6
x = (-7+/-sq.root(49-4*1*-6))/2
=(-7+/-sqrt(49+24))/2
=(-7+/-sqrt(73))/2
we will not be able to proceed further, since there may be some problem in the question
2007-05-18 08:17:13
·
answer #5
·
answered by preetha_jayakrishnan 1
·
0⤊
0⤋
x^2 - 9x^2 + 7x + 12
Combine like terms:
-8x^2 + 7x + 12
And unless you want to get daring and factor this (I say factor out -8 first if you're going to do that; one guy claimed to factor this but the answer is wrong) then that's about as simple as it gets.
2007-05-18 08:10:50
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
-10x^2 +7x + 12
2007-05-18 08:08:42
·
answer #7
·
answered by ihatechunli 2
·
0⤊
2⤋
(x+0.86)*(x-1.74)
2007-05-18 08:10:06
·
answer #8
·
answered by Ali 1
·
0⤊
1⤋